+0  
 
0
46
1
avatar

If 4^x - 4^(x - 1) = 24, then find (2x)^x.

 Jan 10, 2020
 #1
avatar+107405 
+1

4^x  - 4^(x - 1)    = 24         

 

4^x  - 4^x / 4   = 24              multiply through by 4

 

4 * 4^x  - 4^x   = 96

 

3* 4^x     =  96          divide  both sides  by 3

 

4^x  =   32

 

(2^2)^x  = 32

 

2^(2x)  =  32

 

2^(2x)  = 2^5               equate exponents

 

2x  =5

 

x = 5/2  =   2.5

 

So

 

(2x)^x  = ( 2 * 2.5)^2.5  = 5^(2.5)  = 5^(2 + .5)   = 5^2 * 5^.5 = 25√5

 

 

cool cool cool

 Jan 10, 2020

18 Online Users

avatar